The Sin Index vs. the Socially Responsible Index - Bartkowiak, Marcin; Janik, Bogna (Studia Oeconomica Posnaniensia, 2017)
The article compares the profitability and risk factor of the SINdex (from the so called sin stocks group) with the socially responsible index (SRI) from the Dow Jones (DJSI.US) group. The results were confronted with the results obtained by such conventional indices as the NASDAQ-100 and DJIA. The analysis was conducted for the entire research period, i.e. 16 years (1999-2015) and for separated three-year-long superperiods. The goal of the undertaking was to assess in-vestments in unique passive portfolios pursuant to the profit and risk criteria. It may be assumed that if the ROI in sin stocks portfolios continuously record much higher values than ROI in socially responsible and conventional portfolios, the for-mer ones will constantly enjoy a much greater interest.